Acute effects of therapeutic irradiation for prostatic carcinoma on anorectal function. Issue 1 (1st July 1998) - Yeoh, E K; Russo, A; Botten, R; Fraser, R; Roos, D; Penniment, M; Borg, M; Sun, W M
Abstract : Aim —The incidence of anorectal symptoms after radiotherapy (RTH) for localised pelvic malignant disease is unclear. In addition, the effects of pelvic irradiation on both anorectal motility and sensory function are poorly defined. A prospective study was therefore performed on 35 patients (55–82 years of age) with localised prostatic carcinoma before and four to six weeks after RTH to assess its effects on anorectal function. Methods —Anorectal symptoms were assessed by questionnaire. Anorectal pressures at rest and in response to voluntary squeeze, rectal distension, and increases in intra-abdominal pressure were evaluated with perfused sleeve side hole manometry. Rectal sensation was tested during graded balloon distension. Rectal compliance was calculated by the pressure-volume relation obtained during the testing of rectal sensation. Ultrasound was used to determine anal sphincter structure and integrity. Results —RTH had no effect on anal sphincter morphology. The frequency of defecation increased after RTH (7 (3–21) v 10 (3–56) bowel actions a week; p<0.01). After RTH, 16 patients had faecal urgency and eight faecal incontinence, compared with five and one respectively before RTH (p<0.01 for each). Basal and squeeze sleeve recorded pressures were reduced after RTH (54 (3) v 49 (3) mm Hg (p<0.05) and 111 (8) v 102 (8) mm Hg (p<0.01), before and after RTH respectively; means (SEM)). Rectal compliance was reduced after RTH (1.2 v 1.4 mm Hg/ml, p<0.05). After RTH, threshold volumes for perception of rectal distension were lower in the 16 patients who either experienced faecal urgency for the first time (13 patients) or reported worsening of this symptom (three patients) compared with the remaining patients (34 (4) v 48 (5) ml respectively, p<0.05). Conclusion —Faecal incontinence (23%) is a common problem four to six weeks after RTH for prostatic carcinoma and is associated with minor reductions in anal sphincter pressures. The high prevalence of faecal urgency in patients after RTH may be related to alterations in rectal perception of stool.